If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -11 = 47 Reorder the terms: -11 + 2n = 47 Solving -11 + 2n = 47 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 2n = 47 + 11 Combine like terms: -11 + 11 = 0 0 + 2n = 47 + 11 2n = 47 + 11 Combine like terms: 47 + 11 = 58 2n = 58 Divide each side by '2'. n = 29 Simplifying n = 29
| 6+6+6=3x | | x^3-32x+35=0 | | 1.05s-0.01(584.8-s)=28.26s | | 1/4(x-7)=2(3x+12) | | 3x=-5y+15 | | n-8=25 | | 8[8-(-2x-7)]=112x+456 | | (-6x^5y)(-2x^12y^4)=0 | | -28.5=4.5a-4a | | 10k^2-61k+6=0 | | (7x+3)(x-6)=0 | | 11(9c-1)-4=97c+11 | | 5*0.166666666=a | | 8-21=75 | | 8(3+y)=4x-y | | 5+3=22 | | N-3=11+3 | | -8(7-3y)=-18 | | 12=5-8m | | 6b^2+35b+36=0 | | 3x=-y+4500 | | -6(4x+7)+x= | | 2(5x+3)+3x= | | 3x-y+33=0 | | 4.6r-3.2=3.2r-3.9 | | M^0n^6=0 | | 3x+100=-5x+900 | | 7x+28=70 | | 7x+14=2x+18 | | 14-18=40 | | 54+18x= | | 5.6+2.5=.9r |